The global environmental crisis and environmental principles: a criticism regarding principlism and its application in relation to casuistry - Neves Pinto, Gerson; Korndorfer, Debora Cristiane (REVISTA QUAESTIO IURIS, 2025)
This study seeks to delve deeply into pivotal environmental principles, shedding light on their critical role in preserving an ecologically balanced and health-promoting environment for both current and future generations. The investigation unveils recurring clusters of moral dilemmas, underscoring the paramount significance of these principles in resolving specific ethical quandaries. At its essence, the research tackles the central problem of navigating conflicts between principles in the absence of a shared reference point. In response, the argument posits that judgments in virtue ethics are not universal or prescriptive but rather nuanced and ethical, guiding decision-making through a meticulous analysis of contextual intricacies surrounding each action. The chosen approach for this research is the deductive method, meticulously crafted through a comprehensive review of relevant literature. This review involves an analysis of publications extracted from scientific articles and books. Consequently, the study's contribution lies in the strategic application of principialism, its valuation, and the integration of the concept of the just mean within the realm of bioethics. This relevance is particularly underscored in the face of escalating global warming and the consequential environmental degradation on a global scale.